The Effectiveness of Warm Lemongrass Compress Combined with Guided Imagery for Alleviating Osteoarthritis Pain in the Elderly: A Study in Pétoran Village, Surakarta - Az Zahra, Hasna Afranovia; Prajayanti, Eska Dwi; Haryani, Nur (Al-Hijrah Indonesia, 2025)
Background: Osteoarthritis is a degenerative joint disease commonly experienced by the elderly, causing chronic pain that can reduce quality of life and hinder daily activities. Non-pharmacological approaches such as warm lemongrass compresses and guided imagery are safe alternatives to help reduce pain without the harmful side effects associated with long-term medication use. Objective: This study aims to determine the effectiveness of warm lemongrass compresses and guided imagery techniques in reducing osteoarthritis pain in the elderly in Kampung Petoran RT 02 RW 07, Jebres Village, Jebres District, Surakarta City. Methods: This study used descriptive research with a case study conducted on two elderly respondents with osteoarthritis and moderate pain. The intervention was carried out for 2 consecutive days, each lasting 15 minutes. Results: Following the intervention, there was a reduction in pain levels from moderate to mild. The first respondent experienced a decrease from a scale of 4 to 2, and the second respondent from a scale of 5 to 3. Conclusion: Warm lemongrass compresses and guided imagery effectively reduce osteoarthritis pain in the elderly and can be recommended as a non-pharmacological therapy in geriatric nursing.